1994
DOI: 10.1161/01.res.74.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated vascular response due to endothelial dysfunction and role of the renin-angiotensin system at early stage of renal hypertension in rats.

Abstract: We investigated whether endothelial dysfunction might contribute to the exaggerated vasoconstriction that was induced by the administration of norepinephrine at the early stage of one-kidney, one-clip renal hypertension (1K1C) in rats. We also studied the role of the renin-angiotensin system in this phenomenon. Male Wistar rats were killed 48 hours after the induction of renal artery stenosis or sham operation, and ring preparations of the thoracic aorta were obtained. The isometric contraction and relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
25
1
1
Order By: Relevance
“…For vasoconstriction measurements, the maximum response was taken to be the maximum force (mg) induced by norepinephrine (7,8). The vasodilator response to each dose of drug is expressed as a percent of the level that preceded the preconstriction induced by norepinephrine (7,8).…”
Section: Alterations In Endothelium-dependent Vascular Responses In Kmentioning
confidence: 99%
“…For vasoconstriction measurements, the maximum response was taken to be the maximum force (mg) induced by norepinephrine (7,8). The vasodilator response to each dose of drug is expressed as a percent of the level that preceded the preconstriction induced by norepinephrine (7,8).…”
Section: Alterations In Endothelium-dependent Vascular Responses In Kmentioning
confidence: 99%
“…These major cardiovascular effects are mediated by the type 1 angiotensin II receptor (ATR). We have previously reported that angiotensin II receptor blockade protects endothelial function in renal hypertension (6), and type 1 angiotensin II receptor blockers (ARB) have now been widely used as antihypertensive drugs with the expectation of a vascular protective effect (7).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that the vascular smooth muscle cells were intact, the vasodilator response to sodium nitroprusside (10 10 to 10 7 mol/l) was determined. The amount of superoxide necessary to shorten the half-life of endothelium-derived NO was also evaluated by administering lecithinized superoxide dismutase (lecithinized SOD) (0.25 to 4.0 units/l) (19,20). Acetylcholine (Sigma Chemical Co., St. Louis, USA) and LNAME (Calbiochem Co., La Jolla, USA) were dissolved in Krebs bicarbonate solution.…”
Section: Effect Of Cerivastatin On Endothelium-dependent Vascular Resmentioning
confidence: 99%
“…The maximum vasodilator response was defined as the level of vasodilation that preceded the preconstriction induced by norepinephrine. The response to each dose of drug is expressed as a percent of the maximum vasodilation as described previously (19,20).…”
Section: Effect Of Cerivastatin On Endothelium-dependent Vascular Resmentioning
confidence: 99%